HLA-DRB1*0404 is strongly associated with anticalpastatin antibodies in rheumatoid arthritis. Issue 12 (26th February 2007) - Auger, Isabelle; Roudier, Chantal; Guis, Sandrine; Balandraud, Nathalie; Roudier, Jean
Abstract : Objective: To test whether HLA-DR alleles influence the production of particular autoantibodies in rheumatoid arthritis (RA) patients, we screened synovial proteins with sera of RA patients homozygous for different HLA-DR alleles by using 2D blots. We found that sera of RA patients homozygous for HLA-DRB1*0404 recognised a 100-kDa synovial protein identified as calpastatin. We studied B and T cell epitopes on calpastatin and their association with HLA-DRB1*0404. Methods: The frequency of positive sera in patients expressing different RA-associated HLA-DR allele combinations was calculated by inhouse ELISA using purified synovial calpastatin or calpastatin peptides encompassing the entire calpastatin protein as immunosorbent. Interaction between calpastatin peptides and HLA-DR alleles was tested by a direct binding assay. T cell responses to calpastatin were measured in RA patients and controls. Results: We found that RA-associated HLA-DR alleles are associated with presence of autoantibodies to synovial calpastatin in RA patients' sera. HLA-DRB1*0404 is strongly associated with antisynovial calpastatin in RA sera. One linear B cell epitope is preferentially associated with HLA-DRB1*0404. Multiple peptides from calpastatin bind every tested HLA-DR allele associated or not with RA. Peptides from domain 1 and 4 of calpastatin are the best HLA-DR allele binders. The T cell response to calpastatin is frequent in RA patients and independent of the HLA-DR background. Conclusions: HLA-DRB1*0404 is strongly associated with anticalpastatin antibodies in rheumatoid arthritis.